1990
DOI: 10.1007/bf00302086
|View full text |Cite
|
Sign up to set email alerts
|

Psychobehavioral disturbance in epileptic children

Abstract: Psychobehavioral disturbances are frequently seen in epileptic children, but they vary in type and degree. This diversity depends on various factors: age at onset, type of epileptic syndrome and EEG pattern, and the drugs used. The early onset of an epileptic process (within the first year of life) has a profound effect on the organization of primary relational processes and on structuring of the ego. The cognitive and behavioral damage that results may become evident after just a few seizures and may persist … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…This results This study showed an increasing risk of lower intelligence and poor cognitive performance in children with repeated unprovoked seizures regardless of the seizure type, particularly in the presence of higher seizure frequency and severe epileptogenic EEG abnormalities. In accordance, cognitive or behavioral abnormalities were found to be more common in the pediatric population with epilepsy and associated with impairment of memory and ability for new learning, inattention, specific deficits in visuoperceptual domain and visualmotor speed, impairments in executive function, behavioral changes and poor scholastic achievement (5)(6)(7)(8)(9)(10). The etiology of cognitive deficits with epilepsy is multifactorial, being affected by the genetics, type, frequency and severity of seizures, age of onset, duration of illness, location of the epileptogenic lesion, underlying brain abnormality, epileptic syndrome type, and psychosocial issues [14,15,17,43].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This results This study showed an increasing risk of lower intelligence and poor cognitive performance in children with repeated unprovoked seizures regardless of the seizure type, particularly in the presence of higher seizure frequency and severe epileptogenic EEG abnormalities. In accordance, cognitive or behavioral abnormalities were found to be more common in the pediatric population with epilepsy and associated with impairment of memory and ability for new learning, inattention, specific deficits in visuoperceptual domain and visualmotor speed, impairments in executive function, behavioral changes and poor scholastic achievement (5)(6)(7)(8)(9)(10). The etiology of cognitive deficits with epilepsy is multifactorial, being affected by the genetics, type, frequency and severity of seizures, age of onset, duration of illness, location of the epileptogenic lesion, underlying brain abnormality, epileptic syndrome type, and psychosocial issues [14,15,17,43].…”
Section: Discussionmentioning
confidence: 98%
“…It has been shown that seizures selectively impair myelin formation as their effect on brain growth [4,5]. The presence of epilepsy and its treatment during a period of maximal white-matter growth could result in impairment in spatial learning, memory processes and other aspects of cognition [6][7][8][9][10]. Cognitive impairment even if trivial may adversely affect the child's psychosocial functioning in daily life as educational skills and learning tasks.…”
Section: Introductionmentioning
confidence: 99%
“…L eonard and M. R. M. George ures have no neurocognitive de® cits [42]. Even if seizures are well controlled, children and adolescents with epilepsy may function less well than expected in school, family and community activities.…”
Section: Neuropsychological De® Cits In Children With Epilepsymentioning
confidence: 99%
“…Depending on the relative vulnerability of various parts of the brain and individual susceptibility, the consequences of epileptiform discharges may be di erent even if the age of onset, seizure type, severity and duration all appear to be the same [44]. Cognitive disturbances in epileptic children vary depending on the age of onset, seizure type, EEG pattern and selection of anticonvulsants [42].…”
Section: Cognition In Children and Antiepileptic Drugs (Aeds )mentioning
confidence: 99%
“…Both phénobarbital and phenytoin may cause cognitive and behavioral deficits in children. Phénobarbital has been shown to cause hyperac tivity, lowering of IQ, and clinical depression [16][17][18][19], Phenytoin can also lower IQ and may be associated with a progressive encephalopathy [17,20,21]. In addi tion, it causes gingival hyperplasia, hirsutism, coarsening of facial features, and is teratogenic [22,23].…”
Section: Introductionmentioning
confidence: 99%